Pemikiran Pendidikan Karakter Guru Sekumpul - Muhammad Nurkholis Kholik; M. Yunus Abu Bakar; Ali Mas’ud (Universitas Negeri Jakarta, 2025)
This article discusses the concept of Islamic moral education in the thought of KH. Zaini Abdul Ghani, better known as Guru Sekumpul, is a response to modern social dynamics characterized by moral degradation among the younger generation. This research uses a qualitative approach with the literature study method, which examines his lectures, works, and educational practices. Guru Sekumpul offers a noble morality-based character education approach rooted in Sufistic values and Islamic spirituality, with the aim of forming a perfect human being (insan kamil). His thoughts were chosen because of their wide influence and are still felt today. Some findings, such as the emergence of the Abah Guru social volunteer community at the haul event, seem to address modern social issues that are increasingly distant from humanistic values. These findings are also highly relevant to addressing the moral challenges of modern society through an emphasis on exemplary behavior, gentleness, and holistic spiritual guidance.